2014
DOI: 10.1097/qad.0000000000000386
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced immune activation linked to endotoxemia in HIV-1 seronegative MSM

Abstract: Summary This study assessed cellular and soluble markers of immune activation in HIV-1-seronegative men who have sex with men (MSM). MSM immune profiles were characterized by increased expression of CD57 on T cells and endotoxemia. Endotoxin presence was linked to recent high-risk exposure and associated with elevated cytokine levels and decreased CD4/CD8 T cell ratios. Taken together, these data show elevated levels of inflammation linked to periods of endotoxemia resulting in a significantly different immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 20 publications
(18 reference statements)
3
34
0
Order By: Relevance
“…PBMCs were stained with antibody panels testing for T cell activation [33] and monocyte/DC characteristics [34] as previously described. Details of antibodies and stains used in each panel are listed in Supplementary File 1.…”
Section: Methodsmentioning
confidence: 99%
“…PBMCs were stained with antibody panels testing for T cell activation [33] and monocyte/DC characteristics [34] as previously described. Details of antibodies and stains used in each panel are listed in Supplementary File 1.…”
Section: Methodsmentioning
confidence: 99%
“…We recently reported a high incidence of subclinical endotoxemia in a cohort of HIV negative men (20). Endotoxin levels detected in this particular cohort were comparable to those observed in HIV-positive individuals (Supplemental Figure S1), making this study population ideal for modeling in vivo effects of subclinical endotoxemia on immune cell function in the absence of HIV infection and associated viral effects.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported on a cohort of HIV negative men with subclinical endotoxemia that correlated with decreased CD4/CD8 T cell ratio, elevated plasma cytokine levels and markers of T cell exhaustion (20). Using this HIV negative population as an in vivo model of subclinical endotoxemia in the absence of confounding HIV infection and associated viral effects, we assessed the effects of subclinical endotoxemia on cellular immune functions ex vivo .…”
Section: Introductionmentioning
confidence: 99%
“…Compared to people living with HIV (PLHIV), similar or lower levels of IA were reported in HESN [14] [15] [16] [17]. Compared to HIV-neg Controls, some studies reported higher levels of IA in HESN [11] [16] [18] [19] while others reported lower levels [20]- [25], To gain further insight into IA in serodiscordant couples, we aimed to compare the levels (using beta 2 microglobulin (β 2 m) as a soluble marker of IA) between HESN, their HIV+ counterparts and HIV-neg Controls; then analyze the association of IA levels and sexual exposure to HIV (SEHIV).…”
Section: Introductionmentioning
confidence: 99%